Analysis of G-Protein coupled receptor gene of Capripoxvirus from sheep in Saudi Arabia - Abdellatif, M. Magzob; Alsharari, A. Anwar; Ali, Y. Hassan; Kamil, S. Intisar; El‑Sayed, M. Helal (Diponegoro University, 2025)
Capripox is a highly infectious, often fatal, illness that results in severe losses; it is caused by Capripoxvirus (CaPVs) of the Poxviridae. It is challenging to distinguish between members of the CaPVs, even if the infection may be diagnosed based on the clinical picture. The objective of the study was to analyze G-protein Coupled Receptor gene identified from Sheep Capripoxvirus in Rafha. Saudi Arabia. Sequence alignment revealed multiple substitutions in the nucleotides and their deduced ami-no acids. Identity of the GPRC gene sequence among local strains was estimated to be 96.7-100%, whereas homology among selected CaPVs was found to be 88.0-100%. Evolutionary divergence anal-ysis showed a discrepancy of 0.0 to 0.03% among local viruses and 0.0 up to 0.94% related to homolo-gous CaPVs included. Phylogeny displayed CaPVs into three groups; local strains scattered into four branches together with other SPPVs from Saudi Arabia, while the second clustered SPPVs from Saudi Arabia, Iraq and Nigeria and the third includes GTPVs and LSDVs. Analysis showed that at least four variants of CaPVs are circulating among sheep in the region. Molecular analysis will help to identify the involved strains to adopt effective preventive measures.